2008
DOI: 10.1002/bjs.6053
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-like growth factor I improves aspects of mycophenolate mofetil-impaired anastomotic healing in an experimental model

Abstract: Exogenous IGF-I improves some aspects of MMF-impaired anastomotic healing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 27 publications
(34 reference statements)
1
8
0
2
Order By: Relevance
“…Besides collagen formation, mucosal growth is a key factor in early healing of colonic anastomoses. The correlation between mucosal growth and mechanical stability of the anastomoses has been demonstrated in pertinent publications where anastomotic healing was assessed under different conditions. The present results show that mucosal thickness of the target segment of the colon was increased significantly in animals where the anastomosis was performed using oxygen‐producing suture material compared with the untreated off‐the‐shelf thread.…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations
“…Besides collagen formation, mucosal growth is a key factor in early healing of colonic anastomoses. The correlation between mucosal growth and mechanical stability of the anastomoses has been demonstrated in pertinent publications where anastomotic healing was assessed under different conditions. The present results show that mucosal thickness of the target segment of the colon was increased significantly in animals where the anastomosis was performed using oxygen‐producing suture material compared with the untreated off‐the‐shelf thread.…”
Section: Discussionsupporting
confidence: 66%
“…This can rightly be regarded as a flaw of the study. The authors did not include these data in the statistical analysis, as from previous experience a substantial difference in the clinically apparent leakage rate would not be expected between the different treatment groups in the experimental model used. Moreover, adhesions are not supposed to develop within the first 7 days after surgery, unless there is contained leakage or intra‐abdominal sepsis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The overall colonic leakage rate was at 2.4-3.5% according to previous clinical reports [1,2,3,4]. Some methods, such as omentoplasty [5], covering fibrin glue [6], matrix metalloproteases inhibitors [7], [8] and some exogenous agents [9,10,11,12,13] were experimented to decrease the leakage rate. De Hingh et al [14] constructed anastomosis in the distal ileum or distal colon of rats and found matrix metalloproteinases (MMPs) upregulated in the anastomosis postoperatively and Shaper et al [15] had similar results in performing anastomosis at the distal colon of rabbits.…”
Section: Introductionmentioning
confidence: 99%